Annual Plan 2004-2005 (Volume -V) Scheme - Wise Plan Outlay National Capital Territory of Delhi - Planning Commission (Planning Commission, 2004)
Annual Plan 2004-05- Approved outlay of GNCT of Delhi Scheme Wise approved outlay under Annual Plan 2004-05 of Govt. of NCT of Delhi.
Planning Department, Government of National Capital Territory of Delhi